Plant-Derived Trimeric CO-26K-Equivalent Epitope Induced Neutralizing Antibodies Against Porcine Epidemic Diarrhea Virus - Ho, Thuong Thi; Nguyen, Giang Thu; Pham, Ngoc Bich; Le, Van Phan; Trinh, Thi Bich Ngoc; Vu, Trang Huyen; Phan, Hoang Trong; Conrad, Udo; Chu, Ha Hoang (Frontiers in Immunology, 2020)
Porcine epidemic diarrhoea virus (PEDV) is a causative agent of a highly infectious disease with a high mortality rate, especially in newborn piglets in Asian countries resulting in serious economic loss. The development of a rapid, safe, effective, and cost-efficient vaccine is crucial to protect pigs against PEDV infection. The COE antigen is regarded to be a major target for subunit vaccine development against PEDV infection. The naturally assembled COE protein forms a homotrimeric structure. In the present study, we successfully produced a trimeric COE protein as a native structure by fusion with the C-terminal isoleucine zipper trimerization (GCN4pII) motif in Nicotiana benthamiana, with a high expression level shown via semi-quantified Western blots. Trimeric COE protein was purified via immobilized metal affinity chromatography (IMAC), and its trimeric structure was successfully demonstrated by a cross-linking reaction, and a native PAGE gel. A crude extract containing the COE trimer was used for evaluating immunogenicity in mice. After 1 and 2 booster immunizations, the crude extract containing trimeric COE elicited elevated PEDV-specific humoral responses, as demonstrated by ELISA and Western blot analyses. Notably, a virus-neutralizing antibody assay indicated that the neutralization activities of sera of mice vaccinated with the crude extract containing COE-GCN4pII were similar to those of mice vaccinated with a commercial vaccine. These results suggest that crude extract containing trimeric COE is a promising plant-based subunit vaccine candidate for PEDV prevention.